2016
DOI: 10.3390/toxins8040104
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Enterotoxigenic Potential and Determination of Clonal Profile in Staphylococcus aureus and Coagulase-Negative Staphylococci Isolated from Bovine Subclinical Mastitis in Different Brazilian States

Abstract: Epidemiological studies have identified Staphylococcus aureus as the most common agent involved in food poisoning. However, current research highlights the importance of toxigenic coagulase-negative staphylococci (CoNS) isolated from food. The aim of this study was to characterize Staphylococcus spp. isolated from cows with bovine subclinical mastitis regarding the presence of genes responsible for the production of staphylococcal enterotoxins and of the tst-1 gene encoding toxic shock syndrome toxin 1, and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 30 publications
7
18
4
Order By: Relevance
“…The tsst gene was identi ed in 25% of CoNS species including 28.6% of S. epidermidis, 21.6% of S. haemolyticus and 20% of S. saprophyticus strains. In contrary with our work, other studies have found tsst gene in any of CoNS species isolated from newborns and cows with bovine mastitis (32,37). But this gene has been detected in 87% of S. aureus isolated from wound and blood cultures and in 15.5% of S. aureus obtained from bovine mastitis milk (38,39).…”
Section: Disscusioncontrasting
confidence: 99%
“…The tsst gene was identi ed in 25% of CoNS species including 28.6% of S. epidermidis, 21.6% of S. haemolyticus and 20% of S. saprophyticus strains. In contrary with our work, other studies have found tsst gene in any of CoNS species isolated from newborns and cows with bovine mastitis (32,37). But this gene has been detected in 87% of S. aureus isolated from wound and blood cultures and in 15.5% of S. aureus obtained from bovine mastitis milk (38,39).…”
Section: Disscusioncontrasting
confidence: 99%
“…In previous studies, the occurrence of the seg and sei genes varied. Mello et al (22) detected the seg gene only for 1% of S. aureus and 2% for central nervous system isolates, and sei was detected for 11 and 3% for S. aureus and coagulase-negative isolates, respectively. In contrast, Srinivasan et al (30) detected seg and sei with higher frequencies (60.3% for sei and 24.4% for seg).…”
Section: Discussionmentioning
confidence: 99%
“…Most often, bovine mastitis is associated with superantigens or enterotoxins produced by S. aureus (19)(20)(21) or coagulasenegative staphylococci (22). Staphylococcal enterotoxin C is the most common cause of bovine mastitis (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Part of these contaminations results from shedding of S. aureus by infected mammary glands. Several studies have found that the majority of S. aureus mastitis isolates carry at least some of the enterotoxin-encoding genes, although with a wide variation in prevalence and enterotoxin profile (Larsen, Aarestrup, & Jensen, 2002;Mello et al, 2016;Ote, Taminiau, Duprez, Dizier, & Mainil, 2011). Foodborne infection risk is low in the countries where pasteurization is applied to most milk products, but there exists a risk with raw milk and products made with raw milk.…”
Section: Host Range and Zoonotic Potentialmentioning
confidence: 99%